Evaluation of Causative Microorganisms and their Antibiotic Sensitivity Patterns in Chronic Suppurative Otitis Media at Combined Military Hospital, Hyderabad, Sindh - iftikhar, Maryam; Akbar, Farhan (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To determine frequency of causative microorganisms and their antibiotic sensitivity patterns in chronic suppurative otitis media (CSOM).Study Design: Cross sectional study.Place and Duration of Study: ENT Department, Combined Military Hospital, Hyderabad Pakistan, from May 2023 to May 2024.Methodology: A total of 101 male and female patients aged above 15 years who were diagnosed as cases of chronic suppurative otitis media with otorrhea through tympanic membrane perforation were included in the study. Patients were assessed for the causative organism along with its antibiotic sensitivity pattern using standardized techniques.Results: Median age was 30.00 (50.00 – 16.00) years. There were 64(63.37%) male and 37(36.63%) females. Most common causative organism was Pseudomonas aeruginosa found in 51(50.50%) followed by Proteus 27(26.73%). Highest sensitivity was detected for Meropenem 79(78.22%) followed by Cefepime 70(69.31%), Cefoperazone – Sulbactam 68(67.33%), Imipenem 58(57.43%), Piperacillin – Tazobactam 58(57.43%) and Rifampicin 52(51.49%).Conclusion: Most common organisms causing Chronic Suppurative Otitis Media are Pseudomonas aeruginosa and Proteus. Highest sensitivity was observed for meropenem and cefepime while highest resistance was observed against methicillin, co-amoxiclav and tobramycin.